Clinical outcome analysis of patients with autism spectrum disorder: analysis from the UK Medical Cannabis Registry. (September 2022) - Erridge, Simon; Kerr-Gaffney, Jess; Holvey, Carl; Coomber, Ross; Barros, Daniela A. Riano; Bhoskar, Urmila; Mwimba, Gracia; Praveen, Kavita; Symeon, Chris; Sachdeva-Mohan, Simmi; Sodergren, Mikael H.; Rucker, James J.
Introduction: Cannabis-based medicinal products (CBMPs) have been identified as a promising novel therapeutic for symptoms and comorbidities related to autism spectrum disorder (ASD). However, there is a paucity of clinical evidence of their efficacy and safety. Objective: This case series aims to assess changes to health-related quality of life and the incidence of adverse events in patients treated with CBMPs for associated symptoms of ASD enrolled on the UK Medical Cannabis Registry (UKMCR). Methods: Patients treated with CBMPs for ASD-related symptoms for a minimum of 1 month were identified from the UKMCR. Primary outcomes were changes in validated patient-reported outcome measures [Generalised Anxiety Disorder-7 (GAD-7), Single-Item Sleep Quality Scale (SQS), 5-level version of the EQ-5D (EQ-5D-5L) index values] at 1, 3 and 6 months compared with baseline. Adverse events were recorded and analysed. Statistical significance was determined by p < 0.050. Results: Seventy-four patients with ASD were included in the analysis. The mean age of participants was 32.7 (±11.6) years. There were significant improvements in general health-related quality of life and sleep as assessed by the EQ-5D-5L, SQS and GAD-7 at 1 and 3 months, with sustained changes in EQ-5D-5L and SQS at 6 months ( p < 0.010). There were 180 (243.2%) adverse events reported by 14 (18.9%) participants. If present, adverse events were commonly mild ( n = 58; 78.4%) or moderate ( n = 81; 109.5%), rather than severe ( n = 41; 55.4%). Conclusion: This study demonstrated an associated improvement in general health-related quality of life, and anxiety- and sleep-specific symptoms following initiation of treatment with CBMPs in patients with ASD. These findings, while promising, are limited by the confines of the study which lacks a control arm and is subject to attrition bias. Therefore, further evaluation is required with randomised controlled trials.